(untitled) (Journal of Libya for geographical studies, 2022)
The study aimed to use the capabilities and tools provided by GIS, especially the Surface tools, which are one of the toolbox tools in the Toolbox Arc interface, which is one of the most important interfaces of the Arc GIs program specialized in various types of analyzes, in order to elicit and analyze some of the terrain characteristics of the Zarok municipal branch and represent them In the form of digital maps showing the surface topographical phenomena such as the general shape of the area, the levels of the land slope, and the elevation levels, by analyzing a digital elevation model for the area, the study showed that the height of the area ranges between 9 and 160 meters with an average height of 81 meters, and that 87.5% of its surface tends In varying degrees and directions